2023
DOI: 10.3390/nu15040903
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Strategies to Manage Malnutrition and Sarcopenia following Liver Transplantation: A Narrative Review

Abstract: Persisting or newly developed malnutrition and sarcopenia after liver transplant (LT) are correlated with adverse health outcomes. This narrative review aims to examine the literature regarding nutrition strategies to manage malnutrition and sarcopenia after LT. The secondary aims are to provide an overview of the effect of nutrition strategies on the incidence of infections, hospital length of stay (LOS), acute cellular rejection (ACR), and mortality after LT. Four databases were searched. A total of 25 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…The extent of parental and familial awareness of nutrition is a factor that directly affects the formulation and implementation of dietary plans for such patients. Following a liver or kidney transplant, patients encounter several challenges, such as the use of immunosuppressants, 10 inadequate nutrition, 11 and heightened stress levels. In such circumstances, it is important that patients and their families are able to maintain the prescribed dietary pattern for optimal physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of parental and familial awareness of nutrition is a factor that directly affects the formulation and implementation of dietary plans for such patients. Following a liver or kidney transplant, patients encounter several challenges, such as the use of immunosuppressants, 10 inadequate nutrition, 11 and heightened stress levels. In such circumstances, it is important that patients and their families are able to maintain the prescribed dietary pattern for optimal physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding macronutrient deficiencies, protein requirements are increased in both active IBD patients and sarcopenic patients, and intake should be increased to 1.2-1.5 g/kg/d compared to recommendations for general adult population (48,93) . After an inflammatory episode, dietary protein needs in IBD patients may be increased for gastrointestinal mucosal healing, being used as building blocks for macromolecule synthesis in the wounded mucosal area, and for total muscle protein synthesis thus preventing strength decline and sarcopenia (94) .…”
Section: Nutritional-related Interventionsmentioning
confidence: 99%
“…In IBD patients, fat malabsorption is also obser-ved because of decreased reabsorption of bile acids that are deconjugated by bacteria in the colon (48) . However, according to the recent European guidelines, dietary supplementation, e.g., n-3 fatty acids, shall not be advised to support the maintenance of remission in patients with IBD (48) , but may be of interest in the case of sarcopenic patients without IBD (93) . Regarding carbohydrates, some authors consider that supplementation with selected fermenting carbohydrates, promoting specific bacteria and/or metabolites, may be beneficial for IBD patients (48) .…”
Section: Nutritional-related Interventionsmentioning
confidence: 99%
“…Studies suggest the advantages of providing EN vs PN include the preservation of gut structure and function, fewer infectious complications, reduced hospital length of stay, and reduced cost. 65,66 Several studies in patients who underwent liver transplantation have shown benefits of early EN (within 48 h of surgery). [67][68][69][70] Hasse et al 67 and Ikegama et al 68 reported reduced infection rates in patients who received early EN via nasointestinal tubes placed during the transplant surgery.…”
Section: Posttransplant Nutrition Support Posttransplant En Timingmentioning
confidence: 99%
“…EN is preferred over parenteral nutrition (PN) in patients following transplantation who have a functional gastrointestinal tract. Studies suggest the advantages of providing EN vs PN include the preservation of gut structure and function, fewer infectious complications, reduced hospital length of stay, and reduced cost 65,66 . Several studies in patients who underwent liver transplantation have shown benefits of early EN (within 48 h of surgery) 67–70 .…”
Section: Posttransplant Nutrition Supportmentioning
confidence: 99%